2021
DOI: 10.1371/journal.pone.0258397
|View full text |Cite
|
Sign up to set email alerts
|

Plasma electrophoresis profiles of Blanding’s turtles (Emydoidea blandingii) and influences of month, age, sex, health status, and location

Abstract: Baseline plasma electrophoresis profiles (EPH) are important components of overall health and may aid in the conservation and captive management of species. The aim of this study was to establish plasma protein fractions for free-ranging Blanding’s turtles (Emydoidea blandingii) and evaluate differences due to age class (adult vs. sub-adult vs. juvenile), sex (male, female, or unknown), year (2018 vs. 2019), month (May vs. June vs. July), health status, and geographical location (managed vs. unmanaged sites). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
1
0
0
Order By: Relevance
“…Forage items of the two hawksbill aggregations in Florida from this study have not been reported and could also influence size-relevant correlations with plasma protein concentrations. Lastly, we found that temperature and albumin were positively correlated in hawksbills from this study possibly due to higher activity levels and increased food consumption during warming periods, a trend that has also been observed in Blanding's turtles (Emydoidea blandingii) from Illinois (Andersson et al, 2021).…”
Section: Proteinssupporting
confidence: 75%
“…Forage items of the two hawksbill aggregations in Florida from this study have not been reported and could also influence size-relevant correlations with plasma protein concentrations. Lastly, we found that temperature and albumin were positively correlated in hawksbills from this study possibly due to higher activity levels and increased food consumption during warming periods, a trend that has also been observed in Blanding's turtles (Emydoidea blandingii) from Illinois (Andersson et al, 2021).…”
Section: Proteinssupporting
confidence: 75%